Qualidade da água da lagoa Juara (Serra/ES): avaliações físicas, químicas e respostas fisiológicas e citogenéticas em plantas - Duarte, Ian Drumond (2014)
The management of water resources requires the integration of the physical and chemical parameters, and biotic features, which make it possible, identify the combined effects of substances and their influences. The Allium cepa and Tradescatia pallida test systems are used for the study of water pollution from cytogenetic aspects. In addition to these biomarkers, the contents of chlorophyll also are use in studies of stress due to reflection to the single or combined factors. The objective of this study was to evaluate the water quality of the Juara pond (Municipality of Serra / ES) by the integrated analysis of physical, chemical and ecotoxicological aspects through cytogenetic studies in A. cepa and T. pallida, and photosynthetic metabolism in this last specie. Three sampling stations were established along the lagoon. And from water samples, parameters such as conductivity, dissolved oxygen, concentration of nutrients and metals were analyzed. The determination of the metal has occurred by mass spectrometry analysis. The A. cepa test was conducted from seeds germinated in water samples from the pond. With plants of T. pallida, was conducted the test of mitosis in root tip of T. pallida and dosed the pigment contents in fully expanded leaves. For that, assay was performed using the pond water as a solvent for Hoagland solution where previously rooted cuttings of T. pallida were exposed for 24 hours and 40 days for cytogenetic and photosynthetic evaluation, respectively. New test of A. cepa was conducted in the waters of the pond, after 40 days of testing, to assess the maintenance of the chemical properties of the samples. Cytogenetic evaluation in the both species involved the analysis of mitotic index (MI), index of chromosomal aberrations (CA) and frequency of micronuclei (MN). For statistical analysis, analysis of variance followed by Tukey (p <0.05) for the comparison of treatments during the same campaign, and Bonferroni test (p <0.05) for comparison between the campaigns, were used. The measured physical and chemical results show that Juara pond presents evidence of artificial eutrophication. The cytogenetic assays show that two sampling stations, in at least one sampling campaign, showed cytotoxic, genotoxic and mutagenic potentials. However, these potentials do not relate to the contents of Fe and Mn quantified, leading to the idea that these points have other potential pollutants. Cytogenetic damage had maximized effects observed during the second campaign, demonstrating the effect of period of rain on the intensification of pollution in that environment. The study of photosynthetic metabolism in T. pallida showed that the chloroplastidic pigment contents are related to the high input of nutrients on J2 and J3 stations. Being the excess of these, the probable responsible for the less content of pigments in J3. It is observed that the A. cepa and T. pallida tests responded faithfully to the potential environmental risk, complementing the physical and chemical analyzes commonly used in assessing the quality of the lake water environments.